The peculiarities of clinic, diagnostic and surgical treatment of opisthorchous cysts of liver - B. I. Alperovych; G. N. Habas (Бюллетень сибирской медицины, 2002)
The results of inspection and surgical treatment 38 patients with opisthorchiatic cysts of a liver are investigated. Preoperative diagnostics is based on detection opisthorchiasis and specific ultrasonic attributes of these cysts, opisthorchiatic lesion of hepatobiliary system. The complicated current it were marked at 21% of the patients. Carry out 40 operations, including the resections of a liver. Mortality rate was 5,3%. Developed surgical tactics and technique allows to warn specific complications not reducing radicalism of operations.